Jesus and the Leper in Mark 1:40-45: A Biblical Theology Index for the Management of COVID-19 Pandemic - Christopher Naseri (Diacovensia, 2022)
Jesus’ response to the leper’s request in Mark 1:40-45 tempers the harsh reality of laid down protocols for the management of leprosy. Against the physical distance of the time, Jesus takes the risk of touching the leper. He restores his battered dignity, heals him, and shows solidarity. The COVID-19 pandemic has stigmatized the human person as a weapon of infection. This situation has questioned the nature of man as a social being and impeded inter-human relationships. Using the synchronic approach of the historical critical method for the study of this text of Mark, this work compares the challenges of the leper in the ministry of Jesus with the threats posed by COVID-19. It concludes that both situations stereotype the human person and affect interpersonal relationships. It proposes Jesus’ compassionate disposition and sense of solidarity as indices for the management of the COVID-19 crisis.